The Influence of Celebrity Endorser and Product Quality on Purchase Decision Through Brand Image Package PT Aminareka Perdana - Dhamayanty, Stanny; Nokialita, Fitri (Politeknik Pariwisata NHI Bandung, 2023)
This research aims to look at the direct and indirect effects of celebrity endorser, product quality, and brand image on purchasing decisions. The group studied was PT Arminareka Perdana Umrah pilgrims. Samples were taken from 100 respondents randomly. Data collection was carried out by conducting a survey of consumers of Umrah pilgrims. The variables studied were celebrity endorser (X1), product quality (X2), product image (Y), and purchase decision (Z). The data obtained were then analyzed using descriptive methods and path analysis. After the research was carried out, the results obtained were that the variable celebrity endorser (X1) and product quality (X2) had a direct effect on purchasing decisions (Z). Meanwhile, the relationship between celebrity endorser (X1) and product quality (X2) can indirectly affect purchasing decisions. The results of the path analysis test show that the research variable celebrity endorser (X1) influences purchasing decisions through brand image and product quality (X2).